Erratum to the development of uniportal video-assisted thoracoscopic surgery in São Paulo: from diagnosis to lobectomy - de Oliveira, Alexandre; Couto, Thais Amarante P. P. (Journal of Thoracic Disease, 2018)
Erratum to: J Thorac Dis 2017;9:865